STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI DAN KINERJA GURU DI SMP IT AT-TAUFIQ DEPOK TAHUN PELAJARAN 2024/2025 - Sumarni, Sumarni (UNISAN JURNAL, 2025)
Based on this background, the researcher wants to conduct a more in-depth research to find out "The principal's strategy in improving teacher motivation and performance at SMP IT At-Taufiq Depok, Harjamukti Village, Cimanggis District, Depok City, West Java for the 2024/2025 Academic Year". The formulation of the problem in the research a. What are the efforts of the principal in providing motivation and strategies to improve teacher performance at SMP IT AT-Taufiq Depok? b. What obstacles occur in an effort to provide motivation and strategies to improve teacher performance at Smp It At-Taufiq Depok? c. What are the efforts of the principal in overcoming the obstacles that occur in providing motivation and improving the performance of teachers of SMP IT AT-Taufiq Depok? So the main purpose of this study is to analyze the principal's strategy in an effort to improve teacher performance at at SMP IT At-Taufiq Depok. Furthermore, the method used in this study is descriptive-analysis using a qualitative approach. Data collection techniques are through observation, interviews, and documentation. Furthermore, the technique of processing data by describe, analyze and conclude. The results of the research, the principal's strategy in motivating and improving teacher performance at SMP IT At-Taufiq Depok by supervising teachers, controlling attendance, facilitating teachers to participate in competency improvementtraining.